Life time prediction of self-supporting flame-sprayed alumina-rich coatings. Issue 13 (1st July 2021) - Neumann, Marc; Gehre, Patrick; Nwokoye, Rapuruchukwu Ifeyinwa; Jelitto, Hans; Schneider, Gerold A.; Aneziris, Christos G.
Abstract: Main objective of the presented research is the life time prediction of self-supporting flame-sprayed Al2 O3 - and Al2 O3 -ZrO2 -TiO2 -materials under constant load. The characteristic life time and its scatter were derived from stable crack growth tests and Weibull-statistics including the four-point-bending and ball-on-three-balls method. The potential life time was estimated in order to assess room-temperature handling and long term storage of self-supporting flame-sprayed alumina components. In terms of flexural strength, energy release, and subcritical crack growth parameters, distinct differences between both materials were shown. In turn, the characteristic life times only barely deviated from each other. From that the conclusion was drawn that life time performance under constant load application is governed by the characteristic flame-spray microstructure. However, advantages in the flame-spray processing of Al2 O3 - ZrO2 -TiO2 are still given, attributed to its lower melting temperature.